FRI0515 Classic cardiovascular risk factors and minimal disease activity in psoriatic arthritis: results of a spanish multicenter study. (15th June 2017) - Queiro, R; Cañete, JD; Montilla, C; Abad, MA; Montoro, M; Gόmez, S; Cábez, A; Alonso, JC Torre; Ivorra, JA Román; Sanz, J; Salvatierra, J; Calvo, J Alén; et al.
Abstract : Background: Some cardiovascular risk factors (CVRF) have been related to poorer responses to biological therapy 1 . We aimed to evaluate the potential link between the MDA response and the presence of CVRF in patients treated with traditional and/or biological DMARDs. Objectives: The objective has been to evaluate the potential association beetween classic CVRF and the probability of reaching an MDA response in PsA patients. Methods: Cross-sectional study carried out at 25 rheumatology outpatient clinics in patients who fulfilled the Classification for Psoriatic Arthritis (CASPAR) criteria with at least one year disease duration, and treated with biological or conventional synthetic (cs) DMARDs according to routine clinical practice in Spain. Patients were considered in MDA if they met at least 5/7 of the MDA criteria 2 . The relationship between MDA and CVRF was evaluated by uni and multivariate analyses. Results: 227 patients were included, 133 (58.6%) were in MDA state (52% on anti-TNFα monotherapy, 24% on csDMARD monotherapy, 24% on anti-TNFα in combination with csDMARD). Among the classic CVRF, tobacco (crude OR: 0.54), sedentary lifestyle (crude OR: 1.95), hyperuricemia (crude OR: 2.01) and obesity (crude OR: 1.54) were related to the likelihood of MDA in the univariate model (p<0.25). The only CVRF related to the MDA response in the multivariate analysis was a sedentary lifestyle (OR 3.13, 95% CI: 1.50–6.53; p=0.002). We did not find any association between the number of CVRF and the MDA response. Conclusions: Contrary to what has been found in other studies, in this cross-sectional multicenter study we could not find any relationship between traditional CVRF (except for sedentary lifestyle) and MDA. In any case, patients with psoriatic disease should be encouraged to maintain healthy lifestyle habits. References: Ogdie A, Eder L. Improving cardiovascular health and metabolic comorbidities in patients with psoriatic arthritis. Int J Clin Rheumatol 2015; 10(6):451–459. Coates LC, Fransen J, Helliwell PS. Defining minimal disease activity in psoriatic arthritis: a proposed objective target for treatment. Ann Rheum Dis 2010; 69(1):48–53. Acknowledgements: This study was funded by Pfizer. Disclosure of Interest: None declared